Graphene oxide nanocells for impairing topoisomerase and DNA in cancer cells. Issue 26 (11th June 2019) - Nandi, Aditi; Ghosh, Chandramouli; Bajpai, Aman; Basu, Sudipta
Abstract : We have engineered graphene oxide based nanocell to target DNA topoisomerases and nuclear DNA in cancer cells to induce apoptosis. Abstract : DNA topoisomerases and nuclear DNA are important targets for cancer therapy. However, DNA topoisomerase inhibitors and DNA damaging drugs demonstrate a large window of side effects in the clinic. Graphene oxide based biocompatible and biodegradable nano-scale materials have the potential to overcome this complication. However, encompassing different topoisomerase inhibitors along with DNA damaging drugs into 2D-graphene oxide remains a main challenge. To address this, in this manuscript, we have engineered self-assembled spherical 3D-graphene oxide nanoparticles coated with lipid (GO-nanocells) which can concomitantly load and release multiple topoisomerase inhibitors (topotecan and doxorubicin) and DNA damaging drug (cisplatin) in a controlled manner. Fluorescence confocal microscopy confirmed that these GO-nanocells were taken up by HeLa cervical cancer cells and transported into lysosomes temporally over 6 h. A combination of confocal microscopy, gel electrophoresis, and flow cytometry studies revealed that these GO-nanocells damaged nuclear DNA along with topoisomerase inhibition leading to induction of apoptosis through cell cycle arrest in the G2-M phase. These GO-nanocells killed HeLa cancer cells with remarkably greater efficacy compared to a free drug cocktail at 48 h post-incubation. These self-assembled GO-nanocells can serve as a nanoscale tool to perturb multiple therapeutically important sub-cellular targets simultaneously for improved efficacy in future cancer chemotherapy.